Chaos Theory: Implications for Cost Overrun Research in Hydrocarbon Megaprojects - Olaniran, O.; Love, P.; Edwards, D.; Olatunji, Oluwole; Matthews, Jane (American Society of Civil Engineers, 2017)
Cost overruns are a recurrent problem in hydrocarbon (oil and gas) megaprojects. An understanding of why and how they occur is needed if they are to be mitigated; such knowledge can provide managers with the foundations to develop techniques to reduce and contain their negative impacts on a project's performance. This paper examines the nature of cost overruns in hydrocarbon megaprojects using the theoretical lens of chaos theory. The underlying principles of chaos theory are reviewed and its research implications for examining cost overruns identified. By viewing megaprojects as chaotic or dynamic systems, the industry and research community may be better positioned to develop innovative solutions to mitigate cost overrun occurrence.